2020
DOI: 10.1016/j.heliyon.2020.e05349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of powdered and fresh jambu (Acmella oleracea)

Abstract: Jambu, Acmella oleracea (L.), is a low-growing herb plant, with cylindrical, fleshy, decumbent and branched stem varying from 20 to 30 cm in height. It is an abundantly cultivated and consumed vegetable in the northern region of Brazil and usually consumed in preparations of typical foods of the Amazon region. So, this work aimed to compare the chemical composition and physical chemistry of powdered and jambu leaf mass. Acmella oleracea plants were selected, sanitized and their leaves were crushed (without add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…However, the mass of leaves and foam of jambu showed relevant contents of protein (3.39% and 3.3%, respectively) and lipids (0.24 and 0.26%, respectively), so drying led to a reduction in moisture content that contributed to a significant increase in the contents of proteins and lipids, and the lipid content found in the foam after drying was higher than that found in the mass of leaves. Values similar to those obtained here were reported by Gomes et al [16], who found that jambu flours had moisture contents between 4 and 6% w.b. and lipid and protein parameters of 7% and 27%, respectively, with no significant degradation under the studied conditions.…”
Section: Physicochemical Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the mass of leaves and foam of jambu showed relevant contents of protein (3.39% and 3.3%, respectively) and lipids (0.24 and 0.26%, respectively), so drying led to a reduction in moisture content that contributed to a significant increase in the contents of proteins and lipids, and the lipid content found in the foam after drying was higher than that found in the mass of leaves. Values similar to those obtained here were reported by Gomes et al [16], who found that jambu flours had moisture contents between 4 and 6% w.b. and lipid and protein parameters of 7% and 27%, respectively, with no significant degradation under the studied conditions.…”
Section: Physicochemical Characterizationsupporting
confidence: 92%
“…Therefore, Acmella oleracea is a plant of commercial interest, due to its pharmacological properties, but there are few studies assessing its processing and application of conservation methods [15,16]. Thus, the objective of this study was to evaluate the drying kinetics of the mass of jambu leaves and mass of jambu leaves in foam mat at different temperatures (50, 60 and 70 °C and thickness of 1.0 cm), determine thermodynamic properties and evaluate its physicochemical characterization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Roberto et al [ 22 ] observed higher values of moisture content (94.12%) for O. basilicum . Other plant species, typical from the Amazon region, had high moisture contents, such as jambu ( Acmella oleracea ) (92.99%) [ 23 ] and chicory ( Eryngium foetidum ) (87%) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This compound gives the vegetable a flavour with functional properties and astringent characteristics. The leaves have about 89 to 93% water, making it an extremely perishable product [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%